The Publicity Principle in Making the Deed of the Nuptial Agreement by Notary - Mohammad Nizar Sabri (Fakultas Hukum Universitas Hang Tuah, 2018)
The settlement of this research conclude that; the Resolution of Constitutional Council Number 69/PUU-XIII/2015 with regard to nuptial agreements is contradictory to the purpose of the publicity principle. Ratio legis of The authorization related to the publicity of notaries is also contradictory to the obligations of notaries to maintain the confidentiality of the content of a deed and the professional oath of notaries as regulated in Article 16 paragraph (1) letter f of the Amendment to UUJN, in conjunction with Article 4 paragraph (2) of UUJN. The existence of the Letter from the Director General of the Demography and Civil Registry as well as circular letter of the Directorate General of Islamic community guidance (Ditjen Bimasislam) on the registration of Reporting Nuptial Agreements; such letter does not follow up in relation to the resolutions of the Constitutional Council. However, the endeavour made to interpret the resolutions of the Constitutional Council by the Director General of Demography and Civil Registry is inconsistent with the resolution already mentioned by the Constitutional Council (MK). In its first point it is stated that a nuptial agreement can be made drawn up in a notarized deed, on the other hand, the Constitutional Council, in its resolution, only mentions that a nuptial agreement may be drawn up in writing, which means that it may be executed by the parties only or be drawn up as a notarized deed.